MANDIU PASILI IN THE TRADITIONAL WEDDING PROCESSIONS OF THE KAILI TRIBE IN PEVUNU VILLAGE, SIGI REGENCY: SEMIOTIC STUDIES (MANDIU PASILI DALAM PROSESI PERNIKAHAN ADAT SUKU KAILI DI DESA PEVUNU KABUPATEN SIGI: KAJIAN SEMIOTIKA) - Efendi Efendi; Ali Ali; Syamsuddin Syamsuddin; Gusti Ketut Alit Suputra; Anjar Kusuma Dewi; Magfirah Nurul Amalia (Jurnal Gramatika, 2023)
Mandiu Pasili is a part of the traditional ceremony that follows the wedding. Mandiu Pasili (Bathing together in front of the door) is a tradition carried out the morning after the wedding at the bride's residence. The research question is, "How are the symbolic meanings of Mandiu Pasili expressed in the traditional wedding procession of the Kaili tribe in Pevunu Village, Sigi Regency? This research aims to describe the symbolic meanings of Mandiu Pasili in the Kaili tribe's traditional wedding procession in Pevunu Village. The researchers employed a qualitative descriptive research method that gathered data from informants.  Data collection methods include observation, interviews, documentation, recording, and note-taking. The findings of this study indicate that the traditional wedding procession of Mandiu Pasili of the Kaili tribe contains verbal and nonverbal symbolic meanings. The verbal symbol known as Gane (mantra) on Mandiu Pasili, which consists of (1) gane pamula, (2) gane paempu, and (3) gane panggaopu, has the meaning of verbal symbols in the realms of religion, ethics, and philosophy. Examples of nonverbal symbols are examples of eggs, nails, coins, sarongs, young coconuts, flowers, breadfruit leaves, silaguri grass, Mayang coconut blossoms, gold, pots, and machetes. The purpose of implementing the Mandiu Pasili custom is to wish that the newlywed couple (a) can have children, (b)  have a family life that is always harmonious and joyful, (c) keep everyone in good physical andmental health, (d)   to keep disasters away (E) to keep it far away from any potentially harmful influences.